ANALISIS KEAKURATAN KODE DIAGNOSIS RAWAT JALAN DAN IGD (INSTALASI GAWAT DARURAT) DI RSUD KOTA YOGYAKARTA - Rafika Fajarwati; Ristiana Eka Ariningtyas; Ratna Prahesti (Program Studi Perekam Medis & Informasi Kesehatan, 2022)
Background: If the diagnosis is not coded accurately automatically, the resulting data will have a low level of correctness of information. Yogyakarta City Hospital in outpatient and ER services uses RME but in its application until now there has not been a SOP related to coding with RME, the implementation of classification and diagnosis coding using SIMRS based on the ICD-10 desktop version 2010, but there are some officers who use the ICD-10 online version 2010 and some are using ICD-10 desktop version 2015.Objective: To determine the accuracy of outpatient and emergency diagnosis codes based on the 2010 desktop version of the ICD-10 at the Yogyakarta City Hospital.Method: This study used a quantitative descriptive method using a cross sectional approach. The sample taken was part of the outpatient RME and the emergency room at the Yogyakarta City Hospital in the fourth quarter, namely in October -December 2021 which was taken randomly (random sampling) with the Slovin formula.Result: Implementation of disease coding and indexing based on SOP using ICD-10. The coding of outpatient and ER diagnoses at the Yogyakarta City Hospital was in accordance with the observation guidelines. Writing symbols and abbreviations was guided by the SKD of the Yogyakarta City Hospital. A total of 82% (BRME) of diagnosis codes were filled in by coding officers and 18% (BRME) were not filled in. As many as 51% were coded accurately and 49% were not accurate.Conclusion: Implementation of disease coding and indexing is guided by SOPs. The coding was carried out in accordance with the observation guidelines. The writing of symbols and abbreviations was guided by the SKD of the Yogyakarta City Hospital. From the analysis results, more than 50% BRME is complete and accurate.Keyword: RME, Coding, ICD-10, Completeness, Accuracy.